2006
DOI: 10.1111/j.1365-2265.2006.02651.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors predicting final height in early treated congenital hypothyroid patients

Abstract: Our results, obtained in the largest reported available group of congenital hypothyroid patients, show that final height is higher than target height in both sexes and that height at onset of puberty is the main factor affecting final height.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 16 publications
2
14
0
Order By: Relevance
“…In support of this view, in a large Italian cohort of children with CH followedup till the end of their growth, the final height was higher than target height in both sexes. [17] Salerno et al . [13] followed up children with CH diagnosed by screening and treated for > 16 years and reported that the group of children who received higher L-thyroxine dose (> 8 μg/kg/day) at the beginning of therapy attained a final height (0.4 ± 1.0 SDS), which was within the normal range for the reference population but significantly above their target height.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this view, in a large Italian cohort of children with CH followedup till the end of their growth, the final height was higher than target height in both sexes. [17] Salerno et al . [13] followed up children with CH diagnosed by screening and treated for > 16 years and reported that the group of children who received higher L-thyroxine dose (> 8 μg/kg/day) at the beginning of therapy attained a final height (0.4 ± 1.0 SDS), which was within the normal range for the reference population but significantly above their target height.…”
Section: Discussionmentioning
confidence: 99%
“…Even if the CH infants today may have an even better intellectual and neurological prognosis, a subtle impairment of the neurological development and a loss in some IQ points are still detectable [5,18,19,20,21,22,23], whereas the growth is normal in all of them [9,24,25,26,27]. …”
Section: Discussionmentioning
confidence: 99%
“…Early and appropriate treatment during childhood and adolescence prevents the deleterious effects of TH deficiency on growth and bone maturation (86). Several studies on patients treated early for CH have reported normal height growth during childhood and normal adult height, with no effect of initial CH severity on adult height in either sex (87,88,89).…”
Section: Associated Malformations Chronic Diseases and Cardiovasculmentioning
confidence: 99%